2014
DOI: 10.1002/2013rg000434
|View full text |Cite
|
Sign up to set email alerts
|

A review of uncertainty in in situ measurements and data sets of sea surface temperature

Abstract: Archives of in situ sea surface temperature (SST) measurements extend back more than 160 years.Quality of the measurements is variable, and the area of the oceans they sample is limited, especially early in the record and during the two world wars. Measurements of SST and the gridded data sets that are based on them are used in many applications so understanding and estimating the uncertainties are vital. The aim of this review is to give an overview of the various components that contribute to the overall unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
154
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(159 citation statements)
references
References 145 publications
3
154
2
Order By: Relevance
“…The data and quality control of these observations are described in Good et al [36]. In this study, the uppermost temperature observations from the Argo observations have been used, which have a typical depth of 5 m [40] and a very high accuracy, with uncertainties of 0.002 • C [41,42]. Both Argo and drifting buoy observations have previously been used for algorithm development and validation studies [43][44][45][46].…”
Section: In Situ Observationsmentioning
confidence: 99%
“…The data and quality control of these observations are described in Good et al [36]. In this study, the uppermost temperature observations from the Argo observations have been used, which have a typical depth of 5 m [40] and a very high accuracy, with uncertainties of 0.002 • C [41,42]. Both Argo and drifting buoy observations have previously been used for algorithm development and validation studies [43][44][45][46].…”
Section: In Situ Observationsmentioning
confidence: 99%
“…Kennedy [6] submitted that systematic (resulting in uncertainties in the calculated precipitation climatology) and the uncertainty and the spread amongst multiple data sets vary according to regions as well as seasons [15,21,22]. The studies further revealed that uncertainties in the calculated precipitation climatology defined relative to their climatological means are generally larger in the dry regions and/or local dry seasons.…”
Section: Introductionmentioning
confidence: 98%
“…An error in the estimate is the amount of inaccuracy in the estimate compared with a known standard value [3][4][5]. Sources of uncertainty in observational measurements are often broadly categorized as (statistical) random or systematic errors [6,7]. Random observational errors are associated with the observed frequency distributions in the primary data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diurnal variations of upper surface temperature, however, increase during daytime usually within a top of several meters in oceans [15]. In a review of the uncertainty of in situ SST datasets, Kennedy [16] mentioned diurnal variation of temperature as one uncertainty factor and reported that variety in observation time can lead to spurious changes in the data due to the diurnal cycle of temperature. Thus, cases of such uncertainty and pseudo-variability (pseudo-SST fronts) could be contaminated in satellite-based SST data (e.g., [17]).…”
Section: Introductionmentioning
confidence: 99%